Polarizacija mavrične svetlobe - Vilfan, Mojca (Obzornik za matematiko in fiziko, 2023)
We discuss the polarisation of the rainbow light. First a geometric approach combined with numerical calculations is used to explain the appearance of a rainbow. Taking into account Fresnel equations, polarisation degree for a rainbow is obtained.
Keywords: električno polje; Fresnelove enačbe; mavrica; polarizacija; svetloba